THE USE OF BLENDED LEARNING THEORY IN NEGOTIATION TEXT MATERIAL IN HIGH SCHOOL - Roni Nugraha Syafroni (Universitas Muhammadiyah Semarang, 2021)
The background of this research is because I was inspired by the pandemic conditions that hit the country. Students often confide in the researcher. They want material that is contemporary,contextual, not merely textual. Therefore, the researcher took one of the materials about the negotiation text combined with the blended learning theory. The negotiation text that the researcher used was a text about conversation in one hospital, which was sourced from an online news site.The method that researcher use in this research is descriptive analysis. The researcher took the blended learning literature by Wasis D Dwiyogo. The results of this study indicate that blended learning is beneficial when it is translated into negotiation text material. Last but not least, the conclusion of this research shows that blended learning is beneficial when combined with negotiation text material.